Implementing the Kids’ Athletics Program in the System of Increasing the Level of Physical Performance of Youth - Jakubík, Ján; Broďáni, Jaroslav (Physical Education Theory and Methodology, 2025)
Objectives. The objective of this study was to verify the impact of the IAAF project “Kids’ Athletics” on the physical performance of pupils in primary education through the design and implementation of an athletics program. Materials and methods. The present study was conducted using a two-group non-concurrent experiment, in which the experimental group (decimal age 8.64 years) consisted of 50 probands and the control group (decimal age 8.55 years) consisted of 60 probands aged 8-9 years. Additionally, 8 physical abilities tests were used to obtain selected indicators of the level of motor performance and probands’ skill. The effectiveness of the 7-month experimental program was evaluated using comparative analysis through non-parametric statistical methods: Wilcoxon and Mann-Whitney U test and substantive significance assessment: Cohen (r). The difference in the progress of both samples was also determined. Results. From a total of 8 motor tests in the experimental sample, a progress was observed in all 8 cases, of which the following changes were significant in 6 tests: Movement Set with Bar (z = 3.84, p < 0.00, r = 0 .54), Static Pull‑Up Hold (z = 3.53, p = 0.00, r < 0.50), Sit-Up (z = 5.29, p < 0.00, r = 0.75), 3-Way Ball Rolling (z = 4.31, p < 0.01, r = 0.61), the 4×10m Shuttle Run (z = 4.20 m, p < 0.01, r = 0.59) and the Beep Test (z = 4.64, p < 0.01, r = 0.66). In the case of the control group, there was a progress at the level of statistical significance in the Sit-Up (z = 2.87, p < 0.01, r = 0.37), in the 4×10 m Shuttle Run (z = 4.94, p <0.01, r = 0.64) and the Beep Test (z = 2.98, p<0.01, r = 0.38). Conclusions. It has been proven that the “Kids’ Athletics” program, composed of selected disciplines of Kids’ Athletics supplemented by athletic movement games, has a significant impact on a wider range of physical abilities in 8- to 9-year-old children compared to the traditional content of the ISCED 1 state education program. Based on the findings of this study, as well as the comparison of other research works devoted to related issues, it is pointed out the feasibility of implementing such an athletic program into the annual timetables of Physical Education and Sports in primary education at this particular age period.